A Controlled Investigation of Continuing Pain Education for Long-Term Care Staff. (2013) - Ghandehari, Omeed O; Hadjistavropoulos, Thomas; Williams, Jaime; Thorpe, Lilian; Alfano, Dennis P; Bello-Haas, Vanina Dal; Malloy, David C; Martin, Ronald R; Rahaman, Omar; Zwakhalen, Sandra MG; Carleton, R Nicholas; Hunter, Paulette V; et al.
Abstract : BACKGROUND: The underassessment and undertreatment of pain in residents of long-term care (LTC) facilities has been well documented. Gaps in staff knowledge and inaccurate beliefs have been identified as contributors. OBJECTIVES: To investigate the effectiveness of an expert-based continuing education program in pain assessment/management for LTC staff. METHODS: Participants included 131 LTC staff members who were randomly assigned to either an interactive pain education (PE) program, which addressed gaps in knowledge such as medication management, or an interactive control program consisting of general dementia education without a specific clinical focus. Participants attended three sessions, each lasting 3 h, and completed measures of pain-related knowledge and attitudes/beliefs before, immediately after and two weeks following the program. Focus groups were conducted with a subset of participants to gauge perception of the training program and barriers to implementing pain-related strategies. RESULTS: Analysis using ANOVA revealed that PE participants demonstrated larger gains compared with control participants with regard to pain knowledge and pain beliefs. Barriers to implementing pain-related strategies certainly exist. Nonetheless, qualitative analyses demonstrated that PE participants reported that they overcame many of these barriers and used pain management strategies four times more frequently than control participants. CONCLUSIONS: Contrary to previous research, the present study found that the interactive PE program was effective in changing pain beliefs and improving knowledge. Continuing PE in LTC has the potential to address knowledge gaps among front-line LTC providers.